Study of the qualitative composition and quantitative content of phenolic compounds in the Timothy herb - Bondarenko, Ihor; Kyslychenko, Viktoriia (Annals of Mechnikov's Institute, 2023)
Introduction. The high content of phenolic compounds in plants, universal distribution and a wide range of pharmacological properties create the basis for their in-depth study in order to create herbal medicinal products based on them. Little-studied plants with experience in traditional medicine can become a new source of phenolic compounds. Such plants include timothy (Phleum pratense L.) of the Poaceae family. Thymothy herb contains phenolic compounds - coumarins, tannins, flavonoids, etc. Vitamins are represented by ascorbic acid, carotenoids, vitamins of group B, and organic acids, in particular chelidonic and p-coumaric acids, were also detected. The pollen contains the flavonoid dactylin. Timothy herb has been used in traditional medicine for long time as an antimicrobial, immunomodulatory, antipyretic, antirheumatic agent. A herb decoction in the form of herbal baths and wraps helps to increase the elasticity of the connective tissue of blood vessels, activate tissue metabolism. It is also used in the treatment of viral infection, rheumatic pains, arthritis, arthrosis, sciatica, and disorders of kidney and bladder function. Thymothy rhizomes are used as a painkiller against toothache. Thymothy herb is used as nutritious green fodder and hay for domestic animals. However, the study of the chemical composition of thymothy is fragmentary, which does not allow its use in evidence-based medicine. The aim of the work was to perform a comparative study of phenolic compounds in the timothy herb. Materials and methods. The study of hydroxycinnamic acids and flavonoids in timothy herb was carried out by high-performance liquid chromatography (HPLC) on an Agilent 1260 Infinity HPLC System liquid chromatograph. A spectrometric method was used to determine biologically active substances in the studied plant raw materials. Determination of the quantitative content of hydroxycinnamic acids was carried out in accordance with the methodology of the State Pharmacopoeia of Ukraine (SPU) 2.0, volume 3, monograph "Leaves of Nettle"; the content of flavonoids was determined according to the SPU 2.0, Appendix 1, monograph "Flowers of the pagoda tree" method; the content of the sum of polyphenolic compounds was determined according to the SPU 2.0, volume 1, monograph "Determination of tannins in medicinal products of plant origin" method. Results and discussion. As a result of a study, hydroxycinnamic acids and flavonoids were detected in timothy herb by HPLC methods. Chlorogenic acids were identified among hydroxycinnamic acids. Rutin and quercetin were identified among flavonoids. The following flavonoids prevailed in timothy herb content: rutin (before hydrolysis) equaled 326.40±16.28 μg/g and quercetin (after hydrolysis) equaled 500.62±22.31 μg/g. It was determined that the content of timothy herb was dominated by flavonoids (1.08±0.02%), the content of hydroxycinnamic acids was slightly lower (0.73±0.02%), the content of polyphenolic compounds turned out to be insignificant (0.11±0.01 %). Conclusion. Quantitative content of phenolic compounds (hydroxycinnamic acids, flavonoids and polyphenolic compounds in terms of pyrogallol) in timothy herb was determined by spectrophotometry and HPLC techniques. Chlorogenic acid, rutin and quercetin have been identified. It was detected that flavonoids prevailed in terms of content. The obtained data indicate the perspective of further research and, possibly, the future use of timothy herb as a source of phenolic compounds for expanding the domestic plant raw material base of medicinal plants and creating medicinal products on their basis. Keywords: Timothy, Phleum pratense L., phenolic compounds, identification, quantitative content.